Microorganisms in Confined Habitats: Microbial Monitoring and Control of Intensive Care Units, Operating Rooms, Cleanrooms and the International Space Station - Mora, Maximilian; Mahnert, Alexander; Koskinen, Kaisa; Pausan, Manuela R.; Oberauner-Wappis, Lisa; Krause, Robert; Perras, Alexandra K.; Gorkiewicz, Gregor; Berg, Gabriele; Moissl-Eichinger, Christine (Frontiers in Microbiology, 2016)
Indoor environments, where people spend most of their time, are characterized by a specific microbial community, the indoor microbiome. Most indoor environments are connected to the natural environment by high ventilation, but some habitats are more confined: intensive care units, operating rooms, cleanrooms and the international space station (ISS) are extraordinary living and working areas for humans, with a limited exchange with the environment. The purposes for confinement are different: a patient has to be protected from infections (intensive care unit, operating room), product quality has to be assured (cleanrooms), or confinement is necessary due to extreme, health-threatening outer conditions, as on the ISS. The ISS represents the most secluded man-made habitat, constantly inhabited by humans since November 2000 – and, inevitably, also by microorganisms. All of these man-made confined habitats need to be microbiologically monitored and controlled, by e.g. microbial cleaning and disinfection. However, these measures apply constant selective pressures, which support microbes with resistance capacities against antibiotics or chemical and physical stresses and thus facilitate the rise of survival specialists and multi-resistant strains. In this article, we summarize the available data on the microbiome of aforementioned confined habitats. By comparing the different operating, maintenance and monitoring procedures as well as microbial communities therein, we emphasize the importance to properly understand the effects of confinement on the microbial diversity, the possible risks represented by some of these microorganisms and by the evolution of (antibiotic) resistances in such environments - and the need to reassess the current hygiene standards.